Acceleration of drinking pace throughout the evening among frequently drinking young adults in the Netherlands. (20th March 2019) - Groefsema, Martine; Kuntsche, Emmanuel
Abstract: Background and Aims: Previous studies have found that in some countries 'drinking pace' (number of drinks consumed per hour) increases during the course of an evening. We aimed to provide evidence of this acceleration from a culture in which binge drinking is prevalent and to test whether this is consistent across gender, day of week and in high‐risk drinkers. Design: Event‐level data collected on Thursday, Friday and Saturday evenings over 5 consecutive weeks. Setting: The Netherlands. Participants: A total of 197 young adult frequent drinkers (48.7% women, mean age = 20.8). Measurements: High‐risk drinking (assessed by the Alcohol Use Disorders Identification Test) and gender were measured at baseline, and questionnaires were sent to participants' smartphones every hour between 9 p.m. and 1 a.m. A total of 7185 questionnaires during 1589 evenings were used for the analyses. Findings: Multi‐level latent growth curve models revealed an acceleration in drinking on days of the week tested [throughout all evenings; b = 0.430, standard error (SE) = 0.045, P  < 0.001], which stabilized as the evening progressed (b = −0.072, SE = 0.008, P  < 0.001). The temporal pattern did not differ between the days or gender, but men started with a higher number of drinks at the beginning of the evening (b = 0.465, SE = 0.099, P  < 0.001). High‐risk drinking was related to more alcoholic drinks at the beginning of an evening (b = 0.032, SE = 0.011, P  = 0.003) and a steeper acceleration during the subsequent hours (b = 0.021, SE = 0.009, P  = 0.024). Conclusions: Young adults in the Netherlands appear to show an increase in drinking pace during the course of an evening's drinking, with high‐risk drinkers showing a greater increase.